Enrichment of Double RUNX1 Mutations in Acute Leukemias of Ambiguous Lineage - Merati, Gabriele; Rossi, Marianna; Gallì, Anna; Roncoroni, Elisa; Zibellini, Silvia; Rizzo, Ettore; Pietra, Daniela; Picone, Cristina; Rocca, Barbara; Cabrera, Claudia Patricia Tobar; Gelli, Eleonora; Santacroce, Eugenio; et al. (Frontiers in Oncology, 2021)
Acute leukemia of ambiguous lineage (ALAL) is a rare type of leukemia and represents an unmet clinical need. In fact, due to heterogeneity, substantial rarity and absence of clinical trials, there are no therapeutic guidelines available. We investigated the genetic basis of 10 cases of ALAL diagnosed at our centre from 2008 and 2020, through a targeted myeloid and lymphoid sequencing approach. We show that this rare group of acute leukemias is enriched in myeloid-gene mutations. In particular we found that RUNX1 mutations, which have been found double mutated in 40% of patients and tend to involve both alleles, are associated with an undifferentiated phenotype and with lineage ambiguity. Furthermore, because this feature is typical of acute myeloid leukemia with minimal differentiation, we believe that our data strengthen the idea that acute leukemias with ambiguous lineage, especially those with an undifferentiated phenotype, might be genetically more closer to acute myeloid leukemia rather than acute lymphoblastic leukemias. These data enrich the knowledge on the genetic basis of ALAL and could have clinical implications as an acute myeloid leukemia (AML) – oriented chemotherapeutic approach might be more appropriate.